Neohormones as biomarkers of reproductive health - Anand-Ivell, Ravinder; Dai, Yanzhenzi; Ivell, Richard (Elsevier, 2013)
Neohormone systems are defined as evolutionarily new endocrine or paracrine adaptations that supplement basic physiologic functions and define mammalian success. The relaxin family of peptide hormones are typical neohormones. Because they define the specific mammalian aspects of reproductive physiology, such as viviparity with implantation and placentation, lactation, or in the male the necessary adaptations to sperm needed for successful internal fertilization, they offer excellent biomarkers for characterizing reproductive health and disease. For example, ovarian H2-relaxin aids implantation and the establishment of the placenta, and circulating levels are significantly altered in early miscarriage. In the fetus, testicular INSL3 is responsible for the first phase of testicular descent and may be disrupted in cryptorchidism. In the adult, INSL3 is believed to be involved as an antiapoptotic factor in germ cell survival (male) and follicle selection (female) and acts as an excellent measure of Leydig cell functional capacity, particularly in the aging male. INSL5 and INSL6 appear also to be involved in the maintenance of adequate spermatogenesis. With the development of robust immunoassays for various relaxin family members, we are progressively gathering baseline information about normal biomarker levels as well as their perturbations in a wide range of reproductive pathologies.